2015
DOI: 10.1210/en.2015-1388
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Functional Characterization of the G Protein-Coupled Receptor Repertoire of Gastric Somatostatin Cells

Abstract: In the stomach, somatostatin (SST) acts as a general paracrine negative regulator of exocrine secretion of gastric acid and pepsinogen and endocrine secretion of gastrin, ghrelin, and histamine. Using reporter mice expressing red fluorescent protein (RFP) under control of the SST promotor, we have characterized the G protein-coupled receptors expressed in gastric Sst-RFP-positive cells and probed their effects on SST secretion in primary cell cultures. Surprisingly, besides SST, amylin and PYY were also highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…These results further indicate that the epigenetic control of key regulators of hormone secretion is cell-type specific. Notably, Ins2-Cre and Sst-Cre mice may exhibit induced recombination in nonislet cells, such as in the brain and in the stomach (50,51). Although we demonstrated that the hyposecretion of insulin and the hypersecretion of somatostatin from pancreatic islets aid in maintaining normal glucose homeostasis ( Figure 1H and Figure 2), the deficiencies of CUL4B in SST-synthesized cells other than islets may also contribute to impaired glucose tolerance in Sst-Cre +/-Cul4b fl/Y mice, a possibility that requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…These results further indicate that the epigenetic control of key regulators of hormone secretion is cell-type specific. Notably, Ins2-Cre and Sst-Cre mice may exhibit induced recombination in nonislet cells, such as in the brain and in the stomach (50,51). Although we demonstrated that the hyposecretion of insulin and the hypersecretion of somatostatin from pancreatic islets aid in maintaining normal glucose homeostasis ( Figure 1H and Figure 2), the deficiencies of CUL4B in SST-synthesized cells other than islets may also contribute to impaired glucose tolerance in Sst-Cre +/-Cul4b fl/Y mice, a possibility that requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…259 This compound inhibited release of ghrelin with micromolar potency, an effect lacking in cells derived from FFA4 knockout mice, and inhibited release of somatostatin from primary mouse gastric mucosal cells. 370 60 ( Figure 27) has been reported as an orally available, small-molecule FFA4 agonist also with high selectivity for FFA4 over FFA1. 325 This compound displayed high potency at human and mouse orthologs of FFA4 in a G q/11 -dependent assay system, while somewhat lower potency was observed in an arrestin 3 interaction assay.…”
Section: Synthetic Ligands For Ffa4mentioning
confidence: 99%
“…12 Moreover, FFA4 is implicated in regulation of glucagon, ghrelin and somatostatin release, representing likely contributing mechanisms of the observed metabolic phenotype. [13][14][15][16] Chart 1. Representative FFA4 agonists…”
Section: Introductionmentioning
confidence: 99%